Genomic Analysis of Korean Patient With Microcephaly - Lee, Jiwon; Park, Jong Eun; Lee, Chung; Kim, Ah Reum; Kim, Byung Joon; Park, Woong-Yang; Ki, Chang-Seok; Lee, Jeehun (Frontiers in Genetics, 2021)
Microcephaly is a prevalent phenotype in patients with neurodevelopmental problems, often with genetic causes. We comprehensively investigated the clinical phenotypes and genetic background of microcephaly in 40 Korean patients. We analyzed their clinical phenotypes and radiologic images and conducted whole exome sequencing (WES) and analysis of copy number variation (CNV). Infantile hypotonia and developmental delay were present in all patients. Thirty-four patients (85%) showed primary microcephaly. The diagnostic yield from the WES and CNV analyses was 47.5%. With WES, we detected pathogenic or likely pathogenic variants that were previously associated with microcephaly in 12 patients (30%); nine of these were de novo variants with autosomal dominant inheritance. Two unrelated patients had mutations in the KMT2A gene. In 10 other patients, we found mutations in the GNB1, GNAO1, TCF4, ASXL1, SMC1A, VPS13B, ACTG1, EP300, and KMT2D genes. Seven patients (17.5%) were diagnosed with pathogenic CNVs. Korean patients with microcephaly show a genetic spectrum that is different from that of patients with microcephaly of other ethnicities. WES along with CNV analysis represents an effective approach for diagnosis of the underlying causes of microcephaly.